A comparison of three approaches for the treatment of early- stage thymomas: robot-assisted thoracic surgery, video-assisted thoracic surgery, and median sternotomy - Qian, Liqiang; Chen, Xiaoke; Huang, Jia; Lin, Hao; Mao, Feng; Zhao, Xiaojing; Luo, Qingquan; Ding, Zhengping (Journal of Thoracic Disease, 2017)
Background: This aim of this study was to compare three approaches of extended thymectomy for the treatment of early-stage thymomas, which included robot-assisted thoracic surgery (RATS), video-assisted thoracic surgery (VATS), and median sternotomy (MS) perioperative parameters. Methods: A retrospective study was conducted on 123 patients with early stage thymomas at Shanghai Chest Hospital who underwent extended thymectomy between February 2009 and August 2014. Among them, MS was performed on 37 patients, VATS was performed on 35 patients, and RATS was performed on 51 patients. A series of outcome measures were compared between these three approaches, including operative time, intra-operative blood loss volume, occurrence of intra-operative complications, post-operative pleural drainage duration, post-operative pleural drainage volume, duration of hospital stay, and the incidence of post-operative complications. Results: A series of intra- and post-operative parameters showed significant differences in intra-operative blood loss volume, mean post-operative pleural drainage duration, pleural drainage volume and mean duration of hospital stay. For these parameters, during further analysis, significant differences were also demonstrated for comparisons between any two groups. RATS reduces the post-operative drainage duration and volume (2.88 vs. 3.77 and 4.41 days, P